Undergraduate Medical Education in Bangladesh: Facts & Challenges - Rahman, Md Mahfuzar (Anwer Khan Modern Medical College Journal, 2011)
DOI: 10.3329/akmmcj.v1i1.7451 Anwer Khan Modern Medical College Journal 2010; 1(1): 03